2018
DOI: 10.1007/s12225-018-9783-0
|View full text |Cite
|
Sign up to set email alerts
|

A key to the species of Keetia (Rubiaceae - Vanguerieae) in West Africa, with three new, threatened species from Guinea and Ivory Coast

Abstract: Keetia susu Cheek and K. futa Cheek from the Republic of Guinea, and K. abouabou Cheek from Ivory Coast are described here. Each species is assessed using the IUCN standard as, respectively, Vulnerable, Endangered and Critically Endangered. Each species is illustrated and mapped. A key to the 16 species of Keetia in West Africa (Senegal to Benin) is provided. The number of species of Keetia currently accepted is now known to total 35.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…As a result, many names in Lisowski’s Flore de la Guinée are out of date (Cheek et al 2015), and since its publication about 20 newly discovered species (e.g. Cheek & Haba 2016, Cheek et al 2018b) and many new range extensions have been recorded in Guinea. Where a recently discovered species was chosen for a CAP, the protologue (original scientific publication) has been used as the source for the taxonomic information.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, many names in Lisowski’s Flore de la Guinée are out of date (Cheek et al 2015), and since its publication about 20 newly discovered species (e.g. Cheek & Haba 2016, Cheek et al 2018b) and many new range extensions have been recorded in Guinea. Where a recently discovered species was chosen for a CAP, the protologue (original scientific publication) has been used as the source for the taxonomic information.…”
Section: Methodsmentioning
confidence: 99%
“…Recent surveys in Guinea connected with the Guinea Tropical Important Plant Area programme (TIPAs) have discovered several other new species to science, all of which are threatened. Several of these are like Saxicolella futa, also rheophytes, restricted to fast flowing water habitats, such as Inversodicraea pepehabai Cheek (Cheek & Haba 2016), I. koukoutamba and I. tassing (Cheek et al 2019a), Karima scarciesii (Scott Elliot) Cheek , Lebbiea grandiflora Cheek (Cheek & Lebbie 2018;Couch et al 2019), while others are also found on the sandstone rock of the Futa such as Keetia futa (Cheek et al 2018a), Calophyllum africanum (Cheek & Luke 2016), and Kindia gangan Cheek (Cheek et al 2018b).…”
Section: Recognitionmentioning
confidence: 99%
“…Those recently discovered taxa specific to sandstone substrate in the S part of the Fouta Djalon are Gladiolus mariae Burgt (Burgt & al. 2019), Keetia susu Cheek (Cheek & al. 2018c), Kindia gangan Cheek (Cheek & al.…”
Section: New Species From the Guinea Highlandsmentioning
confidence: 99%